On the internet confirmability of crime of picking quarrels and provoking troubles (International relations and international law Journal, 2020)
Criminal law is an instrument of the state, which protects the interests of society from criminalencroachments, and also prevents crimes. The formulation and interpretation of the criminal law mustfollow the principle of modesty and adhere to the inherent spirit of the criminal law, which is insurmountable.In the criminal law amendment (nine), the crime of “provoking troubles with the Internet”has caused great controversy in academic circles. Dogmatics of law not only explain the specification ofnorms, and need to criticize and guide the legislation, criminal law protection has positive value entity,and it can not be completely separated from the value category, it explores the standard value of theguide itself. This paper, from the four layers of legislation, value, social and political philosophy, dealingwith the crime of provoking troubles and picking quarrels, aiming at exploring the potential presuppositionof “provoking troubles” applied on internet that causes disputes in academical circles. Eventuallycome to conclusion that “provoking troubles crime” used on internet needs not to be abolished, but mustbe used with caution.Key words: legal interest, free of speech, modern crisis, provoking troubles and picking quarrels.